PERKECUALIAN TERHADAP PRINSIP LARANGAN PEMBATASAN KUOTA IMPOR TERKAIT PENANAMAN MODAL DI INDONESIA - Resa Raytiaputri (University of Merdeka Malang, 2016)
The existence of an exception from the principle of prohibition on quantitative restrictions related to investmentsis still not fully reflect justice, especially for developing countries like Indonesia, there is still available areproach for developed countries or there is multinational companies that have the advantage of capital to takeprecedence over their interests, but all back at a venture and the power of a country especially developingcountries to be able to maintain the sovereignty of his own country from excessive imports.Awareness of thedefeat by developing countries regarding technology and capabilities of the product markets of developedcountries, made the consistency policies be importance and rules of legislation as one of protection for Indonesia’snational interests amid global competition especially in the field of international trade in capitalinvestment.Considering the capital investment is also needed by Indonesia as one of the efforts to build thenational economy and it is very related to international trade.